Fiscal equalization schemes and fiscal sustainability - Niklas Potrafke; Markus Reischmann (Center for Economic Studies and ifo Institute (CESifo), 2012)
Fiscal sustainability tests have largely ignored the institutional setting of fiscal policy making. Fiscal equalization schemes in federal states are one such institution. We examine whether German state governments pursue sustainable fiscal policies taking into account fiscal equalization transfers. Using panel data techniques we assess fiscal sustainability by investigating whether the debt-to-GDP-ratio has had a positive influence on the primary surplus (Bohn-model). Distinguishing between different measures of the primary surplus we show that including/excluding fiscal transfers changes the results of the Bohn-model. While fiscal equalization transfers do render the fiscal policy of the states sustainable they also provide the states with incentives to increase government spending which, eventually, might render the entire equalization scheme politically unsustainable.
Keywords: H77; H72; H62; C23; 330; fiscal sustainability; institutions; fiscal equalization schemes; panel data; Finanzausgleich; Länderfinanzen; Nachhaltigkeit; Deutschland